Wireless sensor network with Mesh topology using ZigBee protocol (Research, Society and Development, 2020)
Wireless sensor networks have been applied extensively in home and industrial automation. The objective of this project is to develop a wireless sensor network with Mesh topology using the ZigBee protocol. For the development of the research used a case study, where there is a description of the elaboration of devices and development of a wireless sensor network. The network is equipped with coordinating devices, routers and an end device. As a result, the network was tested in order to validate the ability to restructure and self-organize the Mesh topology based on the protocol used.